TERRITORIES OF LIFE AND LAND-CAPITAL: GIROLAMO DOMENICO TRECCANI'S PERSPECTIVE ON THE LEGAL AMAZÔNIA (Social and Environmental Law Journal, 2025)
The interview with Girolamo Domenico Treccani, a tenured professor at the Federal University of Pará (UFPA), addresses the complex socio-environmental issues of the Legal Amazon, focusing on the territorial dispute between traditional peoples and capitalist land exploitation. Treccani distinguishes "territories of life," understood as cultural and identity spaces of indigenous peoples and quilombolas, from "land-capital," seen as a patrimonial asset for economic exploitation, often with negative environmental impacts. Land grabbing and mining are highlighted as practices fueling land conflicts, exacerbated by inadequate records and land overlaps between public and private properties. The right to prior, free, and informed consultation of traditional populations is seen as fundamental, but often overlooked. Treccani advocates for collective land titling of these populations as a means to ensure territorial protection and combat land speculation. He also emphasizes the importance of integrating land management systems and promoting greater inter-institutional coordination to regularize land in the Amazon. The professor concludes by stating that the Amazon should be recognized as a territory of rights, where biodiversity and sociodiversity coexist and are equally valuable.
Keywords: Territories of Life; Land Grabbing and Mining; Collective Land Titling